Simulated model of RAPID concept: highlighting innate inflammation and liver regeneration. Issue 5 (15th July 2020) - Shi, J H; Yan, X; Zhang, S J; Line, P D
Abstract: Background: The resection and partial liver segment II/III transplantation with delayed total hepatectomy (RAPID) concept is a novel transplantation technique for removal of non-resectable liver tumours. The aim of this study was to establish a simulated RAPID model to explore the mechanism involved in the liver regeneration. Methods: A RAPID model was created in rats involving cold ischaemia and reperfusion of the selected future liver remnant (FLR), portal vein ligation, followed by resection of the deportalized lobes in a second step. Histology, liver regeneration and inflammatory markers in RAPID-treated rats were compared with those in controls that underwent 70 per cent hepatectomy with the same FLR size. The effects of interleukin (IL) 6 and macrophage polarization on hepatocyte viability were evaluated in an in vitro co-culture system of macrophages and BRL hepatocytes. Results: The survival rate in RAPID and control hepatectomy groups was 100 per cent. The regeneration rate was higher in the RAPID-treated rats, with higher levels of IL-6 and M1 macrophage polarization ( P < 0·050). BRL hepatocytes co-cultured with M1 macrophages showed a higher proliferation rate through activation of the IL-6/signal transducer and activator of transcription 3/extracellular signal-regulated kinase pathway. This enhancement of proliferation was inhibited by tocilizumab or gadolinium trichloride ( P < 0·050). Conclusion: The surgical model provides a simulation of RAPID that can be used to study the liver regeneration profile. Surgical Relevance The mechanisms sustaining liver regeneration are a relevant field of research to reduce the 'small for size' liver syndrome when the future liver remnant is not adequate. Several surgical strategies have been introduced both for liver resection and transplant surgery, mostly related to this issue and to the scarcity of grafts, among these the RAPID concept involving the use of an auxiliary segment II/III donor liver that expands to a sufficient size until a safe second-stage hepatectomy can be performed. Understanding the mechanisms and pitfalls of the liver regeneration profile may help in tailoring surgical strategies and in selecting patients. In this experimental model the authors investigated liver histology, regeneration and inflammatory markers in RAPID-treated rats. Graphical Abstract: The mechanism of RAPID-associated liver regeneration and its regulation remains unclear. A RAPID model in rats was developed involving cold ischaemia and reperfusion of the selected future liver remnant, portal vein ligation of the remaining segments during step I, and resection of the deportalized lobes during step II. Enhanced liver regeneration following RAPID was observed and may be related to M1 macrophages through the interleukin 6 pathway. ML, median lobe; LLL, left lateral lobe; RL, right lobe; CL, caudate lobe. RAPID model and liver regeneration.